BvPRR7 is a cold responsive gene with a clock function in beet - O. Omolade; A. E. Müller; C. Jung; S. Melzer (Biologia Plantarum, 2016)
The life cycle of flowering plants is partially defined by environmental cues like day length and temperature. In the model plant Arabidopsis thaliana and temperate cereals, such as barley (Hordeum vulgare) and wheat (Triticum spp.), differences in life cycle control have been associated with a natural variation in FLOWERING LOCUS C (FLC) and VERNALIZATION 1-3 (VRN1-3). In sugar beet (Beta vulgaris L.), variation in vernalization requirement and life cycle is determined by a major gene at the B locus. This gene has recently been identified as a pseudo-response regulator (PRR) gene BOLTING TIME CONTROL 1 (BTC1). A second gene in beet with homology to BTC1 and ARABIDOPSIS PSEUDO RESPONSE REGULATOR 7 (APRR7) in Arabidopsis was identified and termed Beta vulgaris PSEUDO RESPONSE REGULATOR 7 (BvPRR7). We functionally characterized BvPRR7 by transgenic analysis in Arabidopsis and expression profiling during development in beet. We show that BvPRR7 was diurnally regulated and responded to cold. Constitutive expression of BvPRR7 distorted diurnal rhythms and caused late flowering in Arabidopsis suggesting a conserved function of BvPRR7 in clock regulation. Conceivably, the retention of a functional role of BvPRR7 in clock regulation may have facilitated the evolution of a distinct role as major floral regulator of the second PRR7 homolog in beet, BTC1.